EHealth in transplantation. (27th November 2020) - Duettmann, Wiebke; Naik, Marcel G.; Zukunft, Bianca; Osmonodja, Bilgin; Bachmann, Friederike; Choi, Mira; Roller, Roland; Mayrdorfer, Manuel; Halleck, Fabian; Schmidt, Danilo; Budde, Klemens
Summary: eHealth ("electronic" Health) is a new field in medicine that has the potential to change medical care, increase efficiency, and reduce costs. In this review, we analyzed the current status of eHealth in transplantation by performing a PubMed search over the last 5 years with a focus on clinical studies for post‐transplant care. We retrieved 463 manuscripts, of which 52 clinical reports and eight randomized controlled trials were identified. Most studies were on kidney ( n  = 19), followed by liver ( n  = 10), solid organ ( n  = 7), bone‐marrow ( n  = 6), and lung transplantation ( n  = 6). Eleven articles included adolescents/children. Investigated eHealth features covered the whole spectrum with mobile applications for patients ( n  = 24) and video consultations ( n  = 18) being most frequent. Prominent topics for patient apps were self‐management ( n  = 16), adherence ( n  = 14), symptom‐reporting (11), remote monitoring of vital signs ( n  = 8), educational ( n  = 7), and drug reminder ( n  = 7). In this review, we discuss opportunities and strengths of such new eHealth solutions, the implications for successful implementation into the healthcare process, the human factor, data protection, and finally, the need for better evidence from prospective clinical trials in order to confirm the claims on better patient care, potential efficiency gains and cost savings.